KINERJA PEGAWAI DALAM MEMBERIKAN PELAYANAN KEPADA MASYARAKAT DI KANTOR CAMAT RAMBAH KABUPATEN ROKAN HULU TAHUN 2018 - Wildan Zaki Kosasi; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In serving the community in terms of services available in the Rambah Sub-District Head Office, Rokan Hulu Regency, of course, it must be in accordance with the SOP (standard operating procedures). In this case, there are many phenomena such as the large number of Camat Office employees who do not know what they will do. and employees also often absent during working hours.Performance is the ability of a person to carry out his work and the results of his work.Service is an activity carried out by a person or group of people on the basis of material factors through certain systems, procedures and methods in order to meet the interests of others according The type of research used is descriptive research with a qualitative approach.Informants in this matter are people who can provide information directly about the performance of employees in the Rambah District Head Office in Rokan Hulu Regency.The results of this study are that employee performance the nature of public services in Rambah Subdistrict, Rokan Hulu Regency in 2018, Riau Province which was assessed based on achievement criteria, skills, attitude and leadership had shown good results.  Keywords: Employee Performance, Service, Society